2018
DOI: 10.1177/2047487318766580
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal fraction of pro-B-type natriuretic peptide versus clinical risk scores for prognostic stratification in chronic systolic heart failure

Abstract: Background The Seattle heart failure model or the cardiac and comorbid conditions (3C-HF) scores may help define patient risk in heart failure. Direct comparisons between them or versus N-terminal fraction of pro-B-type natriuretic peptide (NT-proBNP) have never been performed. Methods Data from consecutive patients with stable systolic heart failure and 3C-HF data were examined. A subgroup of patients had the Seattle heart failure model data available. The endpoints were one year all-cause or cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…This score assessed the incremental predictive value of NT-proBNP for 1-year all-cause mortality compared with a score containing six clinical variables. 26 Similar to the study reported by Arzilli et al, 16 the inclusion of NT-proBNP did not improve discrimination, but resulted in a significant improvement in reclassification for 1-year mortality risk. 26 Likewise, data from seven prospective studies were used to develop the ELAN-HF score for the prediction of 6-month allcause mortality risk in acute HF.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…This score assessed the incremental predictive value of NT-proBNP for 1-year all-cause mortality compared with a score containing six clinical variables. 26 Similar to the study reported by Arzilli et al, 16 the inclusion of NT-proBNP did not improve discrimination, but resulted in a significant improvement in reclassification for 1-year mortality risk. 26 Likewise, data from seven prospective studies were used to develop the ELAN-HF score for the prediction of 6-month allcause mortality risk in acute HF.…”
supporting
confidence: 67%
“…In conclusion, available evidence supports the utility of BNP and NT-proBNP in risk stratification of HF patients. The present study by Arzilli et al 16 provides further insight into the role of biomarkers by demonstrating an additive value of NT-proBNP to the conventional risk scores. From the clinical perspective, improvement in the ability to 'flag' apparently stable chronic HF patients at high risk could benefit those patients.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…new drugs, CRT/ICD implant, biomarkers, risk factor control, coronary and valvular interventions) have clearly modified the prognosis of heart failure patients also in advanced stages of the disease. 41,44,45 In conclusion, the MECKI score initiative has proven to be a simple, useful tool for risk stratification and for Figure 1. Receiver operating characteristic analysis of the MECKI score.…”
Section: Limitations and Strengths Of The Mecki Scorementioning
confidence: 88%
“…4 Risk prediction among cardiovascular patients is an emerging topic of interest. [5][6][7] To gain insight into the prognosis of heart failure, several clinical risk models were developed, such as the Meta-Analysis Global Group in Chronic heart failure (MAGGIC) and Metabolic Exercise data combined with Cardiac and Kidney Indexes (MECKI) score. 8,9 Both MAGGIC and MECKI scores are internally and externally validated, [8][9][10][11] but their clinical use is limited to specific settings.…”
mentioning
confidence: 99%